2021
DOI: 10.1007/s43939-021-00010-2
|View full text |Cite
|
Sign up to set email alerts
|

Ecological risk of heavy metal in agricultural soil and transfer to rice grains

Abstract: Higher accumulation of heavy metals in food grains is one of the leading problems for carcinogenic effects in the body. That’s why; scientists have taken this problem as a potential indicator for ensuring safe food. The present study was carried out to assess the ecological risk of heavy metals such as nickel, copper, arsenic, lead, and manganese in agricultural soil and transfer status to rice grain. Soil samples were collected from four agricultural fields at different times in the Dumuria Upazila under Khul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
1
4
1
Order By: Relevance
“…This can explain why roots have higher Cu concentrations based on samples collected from the TP and the IP compared to other plant parts. However, the concentration of Cu in soil did not show any significant relationship with rice grains among all study sites (p < 0.05), which is consistent with another study's findings [45]. As per Table 5, the average concentrations of Zn in paddy parts collected at the RP reveal that Zn has accumulated more in the roots than in shoots and grains, with values of 87.28, 24.95, and 51.23 mg/kg, respectively.…”
Section: Heavy Metals In Different Parts Of the Plantsupporting
confidence: 90%
“…This can explain why roots have higher Cu concentrations based on samples collected from the TP and the IP compared to other plant parts. However, the concentration of Cu in soil did not show any significant relationship with rice grains among all study sites (p < 0.05), which is consistent with another study's findings [45]. As per Table 5, the average concentrations of Zn in paddy parts collected at the RP reveal that Zn has accumulated more in the roots than in shoots and grains, with values of 87.28, 24.95, and 51.23 mg/kg, respectively.…”
Section: Heavy Metals In Different Parts Of the Plantsupporting
confidence: 90%
“…Therefore, there is a growing demand to use adsorbents of higher efficiency to remove HMs. Bacteria and nanoparticles have gained vast attention due to their morphological, textural, and structural properties [37]. Bacteria secrete biofilm and exopolysaccharides having negative charges that bind with the HMs and NPs [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sharma [30] found that rice and maize grain were hyperaccumulators for Cr, Co, and Cu in Punjab wetlands, in India. Nonetheless, previous studies have also found low BCF (<1) in Bangladeshi rice grains in [31] and Thai sugarcane leaves/shoots/roots [32]. The soil's organic content, heavy metals content, and plant species contribute to different bioavailability and phytoextraction of the heavy metals from soils.…”
Section: Introductionmentioning
confidence: 93%